Targeting Phosphopeptide Recognition by the Human BRCA1 Tandem BRCT Domain to Interrupt BRCA1-Dependent Signaling. Issue 6 (21st June 2018) - Periasamy, Jayaprakash; Kurdekar, Vadiraj; Jasti, Subbarao; Nijaguna, Mamatha B.; Boggaram, Sanjana; Hurakadli, Manjunath A.; Raina, Dhruv; Kurup, Lokavya Meenakshi; Chintha, Chetan; Manjunath, Kavyashree; Goyal, Aneesh; Sadasivam, Gayathri; et al.
Summary: Intracellular signals triggered by DNA breakage flow through proteins containing BRCT (BRCA1 C-terminal) domains. This family, comprising 23 conserved phosphopeptide-binding modules in man, is inaccessible to small-molecule chemical inhibitors. Here, we develop Bractoppin, a drug-like inhibitor of phosphopeptide recognition by the human BRCA1 tandem (t)BRCT domain, which selectively inhibits substrate binding with nanomolar potency in vitro . Structure-activity exploration suggests that Bractoppin engages BRCA1 tBRCT residues recognizing pSer in the consensus motif, pSer-Pro-Thr-Phe, plus an abutting hydrophobic pocket that is distinct in structurally related BRCT domains, conferring selectivity. In cells, Bractoppin inhibits substrate recognition detected by Förster resonance energy transfer, and diminishes BRCA1 recruitment to DNA breaks, in turn suppressing damage-induced G2 arrest and assembly of the recombinase, RAD51. But damage-induced MDC1 recruitment, single-stranded DNA (ssDNA) generation, and TOPBP1 recruitment remain unaffected. Thus, an inhibitor of phosphopeptide recognition selectively interrupts BRCA1 tBRCT-dependent signals evoked by DNA damage. Graphical Abstract: Highlights: Bractoppin selectively blocks phosphopeptide recognition by the BRCA1 tBRCT domain Bractoppin engages tBRCT residues recognizing pSer, plus an adjacent pocket Bractoppin interrupts BRCA1 tBRCT-dependent cellular signals evoked by DNA damage This work opens avenues to inhibit intracellular signaling by the tBRCT domain family Abstract : Periasamy et al. report the development of Bractoppin, a drug-like inhibitor of phosphopeptide recognition by the BRCA1 tBRCT domain, opening avenues to block intracellular signaling via a family of related targets.